O15.4 Predictors of incorrect HIV care initiation beliefs among people living with HIV/AIDS in chókwè district, mozambique. (14th July 2019) - Hara, Christine; Mcintyre, Anne; Heitzinger, Kristen; Oladapo, Keydra; Casavant, Isabelle; Nelson, Robert; Ujamaa, Dawud; Thompson, Ricardo; Bonzela, Juvencio; Pombal, Fidel De; Languitone, Zacarias; Chivurre, Victor; et al.
Abstract : Background: Early initiation of HIV treatment is crucial to reach epidemic control of HIV/AIDS. We evaluated beliefs about timely HIV care initiation and their predictors to better understand barriers to treatment initiation and inform educational interventions in Mozambique. Methods: We analyzed cross-sectional data collected from the 2014–2017 HIV combination prevention survey in Chókwè District, Mozambique to evaluate the prevalence of and associations with the belief that immediate HIV care after a positive diagnosis is not needed if a patient feels well. Analysis was restricted to HIV-positive participants, aged 15–59 years, who had previously heard of HIV and HIV treatment, had prior knowledge of their HIV-positive status and had ever received HIV care in Chókwè. Descriptive analysis and multivariate logistic regression modeling were used to estimate the adjusted odds ratios (aOR) of potential predictors. All calculations were weighted to reflect the 2013 district census. Results: The median age of participants (N=2167) was 37 years (95% CI: 37–38); twenty-five percent were male, 75% had ever taken treatment and of those, 86% were on treatment at the time of survey. Sixty-two percent of participants believed there was no need to immediately seek HIV care after a positive diagnosis if the patient felt well. Never taking ARVs (aOR=4.1, 95% CI: 3.1–5.5), believing traditional medicine was as good as HIV treatment (aOR 4.2, 95% CI: 1.8–9.8), and never notified by a healthcare provider of their HIV treatment eligibility (aOR 1.4, 95% CI: 1.0–2.0) were associated with an increased odds of this belief. No significant associations with sociodemographic characteristics were found. Conclusion: These results demonstrate the importance of robust HIV treatment and counseling services that reinforce the benefits of early treatment initiation. Implementation of culturally responsive psychosocial support strategies may increase the prevalence of correct HIV care beliefs and treatment initiation. Disclosure: No significant relationships.